Testing procedures for abdominal muscles using the muscle dynamometer SD02 - Malatova, R; Drevikovska, P (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2009)
Abstract The aim of this study was to compare two tests both frequently used for determination of the state of the lumbar spine muscle system during static and dynamic loads. The sit-up test is a commonly used terrain test, while the diaphragm test is a more exact laboratory procedure. For both tests, measurements conducted by the muscular dynamometer SD02 were used to assure congruency in evaluation. The tests are based on the general information that the muscles of the deep stabilizing spine system (DSSS) are interconnected and form one functional unit, and that dysfunction of just one of these muscles may cause total dysfunction of the whole muscle system. It is therefore expected that the participation and force generated by the largest muscles of the area, musculus rectus abdominis and musculus transversus abdominis, will be comparable also during the testing procedures. Forty-five healthy women joined in the research, with the average age of 21.6 years. The results obtained were statistically evaluated using Statistica 6. The results showed the clear incapability of the sit-up test to indicate correctly the imbalances of the muscles of the DSSS, also implying that the tested subjects suffer to a high degree from dysfunctions of the DSSS.